Preferensi Konsumen terhadap Pembelian Buah Golden Melon (Cucumis melo L.) di Taman Hati Farm - Fadilah, Nurul; Suyudi, Suyudi; Mutiarasari, Nurul Risti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Melon fruit has diverse varieties, and the availability of various melon varieties makes melons have a wide market share. Diverse consumer preferences also encourage the creation of various varieties of melons to meet consumer desires and preferences. This study aims to determine consumer preferences for the attributes of golden melon fruit at Taman Hati Farm, analyze differences in consumer preferences towards purchasing golden melon fruit at Taman Hati Farm, and examine the attributes most considered by consumers in making purchasing decisions for golden melon fruit at Taman Hati Farm. The research method used is the survey, the size of the sample is calculated using the linear time function method obtained by 60 respondents, which was carried out by accidental sampling. The study will be conducted from November 2023 to May 2024. The analysis method uses Chi-square analysis and the fishbein multiattribute. The results showed that the attributes of golden melon fruit that became consumer preferences at Taman Hati Farm were that the fruit has no aroma, bright yellow fruit skin color, a very sweet fruit taste, medium-sized fruit (1,27 - 1,71 kg), a crunchy texture of fruit flesh, and prices in the medium category are around (Rp.31,000–Rp.40,000) per kilogram, there is a differences in consumer preferences for the attributes of golden melon fruit, and the attributes that consumers consider in purchasing decisions of golden melons at Taman Hati Farm, they are: size, fruit taste, fruit price, texture of fruit flesh, fruit skin color, and fruit aroma.